ELECTROMAGNETIC MONITORING DURING THE AFTERSHOCK PERIOD OF THE 2003 CHUYA EARTHQUAKE IN THE MOUNTAIN (GORNY) ALTAI: MEASUREMENT METHODOLOGY, RESULTS - A. E. Shalaginov; N. N. Nevedrova (Геодинамика и тектонофизика)
The article considers the method of observations, interpretation of data and results of electromagnetic monitoring with a controlled source for one of the seismically active regions of Siberia – Mountain (Gorny) Altai. The monitoring is carried out during the aftershock period in the epicentral zone of the destructive Chuya earthquake of 2003 with M=7.3. For regular observations, a measurement technique has been developed with several modifications of the transient electromagnetics method (TEM) to determine variations in electrical resistivity and anisotropy coefficient. The long-term series of these two geoelectric parameters of the section are presented, compared with the characteristics of the ongoing seismic events. The analysis shows that variations in electrical resistance and electrical anisotropy reflect the development and gradual attenuation of aftershock activity of a powerful earthquake. The advantages of the TEM method and the chosen methodology for monitoring in complex areas are reflected.